Permasalahan WNI Baik TKI Maupun Non-TKI - Adamhar, Ferry (Indonesian Journal of International Law, 2005)
It is commonly perceived that a State is obliged to provide protection to its citizens, especially those who are having troubles abroad. The Government of the Republic of Indonesia, through the Department of Foreign Affairs and other related Governmental Bodies, has been continuing to upgrade its policy in this field. Based on the Department’s experience, providing protection to Indonesian citizens abroad could be very complicated, especially those who are not covered by official documents. In the last two decade, Indonesia saw increasing problems that involved its citizen abroad. This trend needs a comprehensive solution. In general the cause of these problems in inept management of sending workers abroad, for example, some workers are sent abroad without understanding their contract or without proper preparation training. Consequently, these workers do not comprehend their rights. These workers are keen to be abused by the employer. Providing protection for Indonesian citizens abroad, especially workers, depends on two issues. First, the recruitment process and the procedures of sending the workers. The business does not stop by recruiting and sending the workers, but also making these workers fully aware of their rights as well as the terms and conditions of the job. Second, the domestic situation that influences the effectiveness of providing the needed protection. It needs a well-coordinated policy among related governmental bodies in Indonesia in order to provide best protection for the Indonesian workers abroad. The Indonesian representatives abroad could not execute their duty well in providing protection if the well-coordinated policy does not exist. In dealing with these problems, there are things to do. These include improving the management of employment, empowering the workers by giving proper training and informing their rights, as well as strengthening the coordination among governmental bodies related to this matter.